Predicting the effects of climate change on deep‐water coral distribution around New Zealand—Will there be suitable refuges for protection at the end of the 21st century?. (31st August 2022) - Anderson, Owen F.; Stephenson, Fabrice; Behrens, Erik; Rowden, Ashley A.
Abstract: Deep‐water corals are protected in the seas around New Zealand by legislation that prohibits intentional damage and removal, and by marine protected areas where bottom trawling is prohibited. However, these measures do not protect them from the impacts of a changing climate and ocean acidification. To enable adequate future protection from these threats we require knowledge of the present distribution of corals and the environmental conditions that determine their preferred habitat, as well as the likely future changes in these conditions, so that we can identify areas for potential refugia. In this study, we built habitat suitability models for 12 taxa of deep‐water corals using a comprehensive set of sample data and predicted present and future seafloor environmental conditions from an earth system model specifically tailored for the South Pacific. These models predicted that for most taxa there will be substantial shifts in the location of the most suitable habitat and decreases in the area of such habitat by the end of the 21st century, driven primarily by decreases in seafloor oxygen concentrations, shoaling of aragonite and calcite saturation horizons, and increases in nitrogen concentrations. The current network of protected areas in the region appear to provide little protection for most coral taxa, as there is little overlap with areas of highest habitat suitability, either in the present or the future. We recommend an urgent re‐examination of the spatial distribution of protected areas for deep‐water corals in the region, utilising spatial planning software that can balance protection requirements against value from fishing and mineral resources, take into account the current status of the coral habitats after decades of bottom trawling, and consider connectivity pathways for colonisation of corals into potential refugia. Abstract : Protection of deep‐water corals by networks of marine protected areas may not be effective if altered environmental conditions from climate change shift the distribution of their preferred habitat. Habitat suitability models incorporating future predictions of seafloor conditions identified areas of potential refugia for 12 deep‐water coral taxa at the end of the 21st century. For most taxa, these models predicted substantial shifts in the location of the primary habitat and decreases in its area. For instance, the Kermadec protected area currently provides crucial primary habitat for Enallopsammia rostrata (pictured), but such habitat in this area is predicted to shrink over time.